Patient‐specific determination of change in ocular spherical aberration to improve near and intermediate visual acuity of presbyopic eyes. Issue 4 (9th December 2018) - Shetty, Naren; Kochar, Shruti; Paritekar, Prajakta; Artal, Pablo; Shetty, Rohit; Nuijts, Rudy M. M. A.; Webers, Carroll A. B.; Sinha Roy, Abhijit
Abstract : The purpose was to determine the optimum negative spherical aberration induction required to improve near and intermediate visual acuity (VA) of presbyopic eyes. A total of 174 normal and diabetic (no retinopathy) presbyopic eyes (age ≥ 40 years) were measured with visual adaptive optics simulator (Voptica, Spain). First, baseline uncorrected VA and aberrations were measured. VA at 40 cm (near), 80 cm (intermediate) and distance was measured. Then, a negative spherical aberration (SA) was added to baseline ocular SA, and VA at all targets was reassessed after correction of distance refractive error. Clinically, baseline SA and root mean square of higher order aberrations were similar between the normal and diabetic presbyopic eyes. Baseline VA of the diabetic eyes at near and intermediate was better than the same of normal eyes ( P = 0.001). After SA change, VA at near and intermediate of both normal and diabetic presbyopic eyes improved. However, fewer diabetic eyes needed higher SA change than normal eyes ( P = 0.03). The corresponding trends with change in VA at near and intermediate were also similar between the normal and diabetic eyes. Patient‐specific modulation of ocular SA to improve near and intermediate VA in a large cohort of eyes was successful in improving VA, sometimes even distance VA. Abstract : Presbyopia causes the patient to lose near target reading ability. This is primarily a lenticular problem, where the ocular spherical aberration (SA) increases with age. In this study, a negative SA was induced in the patient's eye using adaptive optics spatial light modulator. The results showed that each eye required a patient‐specific modulation of SA to achieve improvement of near and intermediate vision without compromising distant vision too much.